The Influence of Decision Support Systems (DSS) on Employee Performance at PT. Pratama Indomitra Konsultan - Abdurrahman, Faris Nur; Mahdiana, Deni (Jurnal Manajemen Bisnis, 2024)
This study aims to examine the effect of Decision Support System (DSS) on employee performance at PT Pratama Indomitra Konsultan. This study uses a quantitative causal design with data collected from 88 employees through interviews, document recording, and questionnaires. The data was analyzed using simple linear regression and SPSS 23.0 for Windows. The results of the study show that there is a positive and significant relationship between DSS and employee performance.